Analysis of Indonesia's Maritime Security Strategy and Policy as the World Maritime Axis - Eka Siwi Nurhayati; Widodo Widodo; Budiman Djoko Said; Pujo Widodo; Herlina Juni Risma Saragih (CV. Rayyan Dwi Bharata, 2023)
As the largest archipelago, Indonesia should be able to utilize its potential to create prosperity for its people. In fact, the maritime sector has not been fully utilized by Indonesia. Indonesia must prioritize the goal of becoming a maritime country to restore maritime glory. This is in line with Indonesian President Joko Widodo's goal to make Indonesia the world's maritime axis. The research method used is descriptive qualitative. The World Maritime Axis is indeed a decision taken by the government to restore the nature of Indonesia as an archipelago. Until now, the World Maritime Axis has not taken the form of a document equipped with a strategy in it. The strategy becomes an 'extension' of the policy, which currently there is no World Maritime Axis Strategy because the policy is still overlapping. Currently, the World Maritime Axis is categorized as a development policy discourse whose orientation is to realize Indonesia's vision as a maritime country, so it requires a lot of attention to fix and complete this idea so that it can be categorized as a policy and implemented through a strategy.